Proposal of the Development of a New Invoice Administration on Accounting System at PT Freeport Indonesia - ., Hariswoyo; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2017)
Abstract. This Final Project is concerning about the problem occurred in the Tax and Accounting Department of PT Freeport Indonesia. In tax department one of the biggest cost incurred coming from tax audit result, one caused by wrong deduction in withholding tax transactions. This problem occurred because the system that currently available is still relying on manual recording and processing. The objective of the final project is to provide a new alternative of invoice administration system to be proposed to the management. From the research, the writer concludes there are three process can be improved to be computerized basis, as follows: input data process from manual input to automatic input by using Optical Character Recognition, Withholding Tax deduction checking process from manual checking to Web checking process and document archiving process from manual archive to barcode archiving process. By implementing this final project, the Company will potentially save USD 128.000 per year from miscalculation and around USD 21.000 per year from the time consume efficiency. Furthermore, the availability of supported technology, and the ability of the company to fund this project also become factor to be considered by the company to implement this project. Keyword : Invoice Administration, Tax Review Proses, Decision Making  Abstract. This Final Project is concerning about the problem occurred in the Tax and Accounting Department of PT Freeport Indonesia. In tax department one of the biggest cost incurred coming from tax audit result, one caused by wrong deduction in withholding tax transactions. This problem occurred because the system that currently available is still relying on manual recording and processing. The objective of the final project is to provide a new alternative of invoice administration system to be proposed to the management. From the research, the writer concludes there are three process can be improved to be computerized basis, as follows: input data process from manual input to automatic input by using Optical Character Recognition, Withholding Tax deduction checking process from manual checking to Web checking process and document archiving process from manual archive to barcode archiving process.By implementing this final project, the Company will potentially save USD 128.000 per year from miscalculation and around USD 21.000 per year from the time consume efficiency. Furthermore, the availability of supported technology, and the ability of the company to fund this project also become factor to be considered by the company to implement this project. Keyword : Invoice Administration, Tax Review Proses, Decision Making